Handbook of forensic anthropology and archaeology - Blau, S. (Soren); Ubelaker, Douglas H. (New York : Routledge, 2016)
'With contributions from 70 experienced practitioners from around the world, this second edition of the authoritative Handbook of Forensic Archaeology and Anthropology provides a solid foundation in both the practical and ethical components of forensic work. The book weaves together the discipline's historical development; current field methods for analyzing crime, natural disasters, and human atrocities; an array of laboratory techniques; key case studies involving legal, professional, and ethical issues; and ideas about the future of forensic work--all from a global perspective. This fully revised second edition -provides an updated perspective of the disciplines of forensic archaeology and anthropology; -expands the geographic representation of the first edition by including chapters from practitioners in South Africa and Colombia; -adds exciting new chapters on the International Commission on Missing Persons and on forensic work being done to identify victims of the Battle of Fromelles during World War I'--
'Over the last 10 years, interest in the disciplines of forensic anthropology and archaeology has exploded. In order to provide archaeologists and their students with a reliable understanding of these disciplines, this authoritative volume draws contributions from fifty experienced practitioners from around the world to offer a solid foundation in both the practical and ethical components of forensic work. Over 40 chapters weave together historical development, current field methods in analyzing crime, natural disasters and human atrocities, an array of laboratory techniques, key case studies, legal, professional, and ethical issues, and promising future directions, all from a global perspective. This volume will be the benchmark for the understanding of anthropological and archaeological forensics for years to come. This Handbook is sponsored by World Archaeological Congress'--
Includes bibliographical references and index.
Keywords: Forensic anthropology -- Handbooks, manuals, etc; Forensic archaeology -- Handbooks, manuals, etc; Forensic anthropology -- Case studies; Forensic archaeology -- Case studies